Management of Posterior Segment Intraocular Foreign Body with Vitrectomy; Visual and Anatomical Outcome
AIM: To evaluate the anatomical and visual outcome following removal of intraocular foreign body (IOFB) through pars planavitrectomy. MATERIAL & METHODS: A retrospective analysis of 11 cases of retained posterior segment foreign body that underwent pars planavitrectomy for removal of foreign body during the period of January 2013 to August 2017 was conducted. Demographics of patients, mechanism and details of injury, Snellen best corrected visual acuity, examination results at presentation and after surgery, any diagnostic imaging and surgical procedure were recorded and analysed. RESULTS: Out of eleven eyes of eleven patients (mean age= 25.4